2003
DOI: 10.1046/j.1365-277x.2003.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Snacking patterns influence energy and nutrient intakes but not body mass index

Abstract: These data indicate that snacking patterns have some effects on energy and nutrient intakes but not on BMI. Snack food choices remain a concern, especially beverages, including those that are sweetened. Vegetables and fruits as snacks should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
136
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 34 publications
19
136
1
1
Order By: Relevance
“…To the best of our knowledge, no previous studies have attempted to classify and randomize participants into a weight loss study based on their self-reported snacking status, so there is little precedent to rely upon for guidance. 22 Hampl et al 22 attempted to classify snacking status in an observational study, but only used a crude frequency measure to classify individuals as multiple or never snackers. It is possible that our approach was insensitive or inaccurate in classifying snackers, thus leading to null results with respect to matching snacking status with the use of snacks.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no previous studies have attempted to classify and randomize participants into a weight loss study based on their self-reported snacking status, so there is little precedent to rely upon for guidance. 22 Hampl et al 22 attempted to classify snacking status in an observational study, but only used a crude frequency measure to classify individuals as multiple or never snackers. It is possible that our approach was insensitive or inaccurate in classifying snackers, thus leading to null results with respect to matching snacking status with the use of snacks.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a positive relation between low eating frequency and obesity, [2][3][4][5] whereas other studies found no relation. [6][7][8] Gender differences have also been reported, that is, BMI has been found to be negatively associated with eating frequency in men and positively associated in women. 9,10 Similar inconsistencies have been found in the relation between eating frequency and energy intake, where some studies have reported a positive relation, 10,11 whereas other studies found no relation at all 12 or gender differences.…”
Section: Introductionmentioning
confidence: 98%
“…9 It has been suggested that the inconsistent associations reported between BMI, energy intake and eating frequency/ snacking are due to differences in physical activity. 8,9 Drummond et al 13 hypothesized that the lack of a relationship between increased snacking and BMI may be explained by the fact that frequent snackers may have higher energy intakes due to higher physical activity levels. This implies that those who have a frequent snack intake are more physically active and also maintain normal weight.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations